2022
DOI: 10.1101/2022.03.11.483960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective Control of Parasitic Nematodes Using Bioactivated Nematicides

Abstract: Parasitic nematodes are a major threat to global food security, particularly as the world amasses 10 billion people amidst limited arable land. Most traditional nematicides have been banned due to poor nematode-selectivity, leaving farmers with inadequate controls. Here, we use the model nematode Caenorhabditis elegans to identify a family of selective imidazothiazole nematicides, called selectivins, that undergo cytochrome p450-dependent bioactivation exclusively in nematodes. At low parts-per-million concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Recently, Burns et al (2023), when screening uncharacterized compounds that disrupted the growth of the free‐living nematode Caenorhabditis elegans , discovered a new class of nematicides that contain imidazothiazole, and found that they were highly selective in killing only nematodes (Figure 1A). Experiments using various nematode species and a wide range of non‐nematode species and cell types indicated that the newly discovered nematicides, called selectivins, exhibit even higher selectivity for nematodes than most commercially available formulations tested.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Burns et al (2023), when screening uncharacterized compounds that disrupted the growth of the free‐living nematode Caenorhabditis elegans , discovered a new class of nematicides that contain imidazothiazole, and found that they were highly selective in killing only nematodes (Figure 1A). Experiments using various nematode species and a wide range of non‐nematode species and cell types indicated that the newly discovered nematicides, called selectivins, exhibit even higher selectivity for nematodes than most commercially available formulations tested.…”
Section: Figurementioning
confidence: 99%
“…Recently, Burns et al (2023), when screening uncharacterized compounds that disrupted the growth of the free-living nematode Caenorhabditis elegans, discovered a…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently discovered a novel class of imidazothiazole compounds called the Selectivins that selectivity kill nematodes via cytochrome P450-mediated bioactivation ( 8 ). Xenobiotic-metabolizing cytochrome P450 enzymes (P450s) typically detoxify their substrates, catalyzing monooxygenation reactions that enhance substrate hydrophilicity and promote metabolite excretion via drug efflux pumps ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some substrate-P450 pairs transform a relatively inert compound into a metabolite that exhibits novel or heightened biological activity ( 1012 ). This bioactivation can be phylum or species-selective due to the vast phylogenetic diversity of P450s ( 8 , 13 ). Indeed, we have shown that the Selectivins are selectively bioactivated by specific nematode P450s into reactive electrophilic products that kill nematodes but not non-target species from diverse phyla ( 8 ).…”
Section: Introductionmentioning
confidence: 99%